Peningkatan Hasil Pembelajaran Matematika dengan Metode Penggunaan Media Bangun Ruang Datar pada Siswa Kelas V SDN No.15 Segedong Kabupaten Bengkayang - Nurpidda Nurpidda (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The lack of interest in learning and the impression as a difficult science causes low results in the mathematics learning process, especially at the elementary school level. This prompted research on teaching materials for calculating the area of a simple flat shape and calculating the volume of a cube through the use of media to improve learning outcomes in class V of SDN No 15 Segedong. The purpose of this study was to improve learning outcomes of mathematics through the use of media for geometric shapes and flat shapes in calculating the area of simple flat shapes and the volume of cubes and blocks in fifth grade students of SDN No 15 Segedong, Bengkayang Regency, West Kalimantan. The research is based on classroom action research (PTK) through the stages of observation, field observation and evaluation. This research activity was carried out in 2 cycles, where the evaluation in the first cycle showed the average score of the 14 students was 63.70, an increase in the evaluation results of the second cycle, which was 76.65 From this research, it shows that the use of learning media in calculating the area of the shape and volume of the cube can improve learning outcomes.